2020
DOI: 10.1161/circheartfailure.119.006573
|View full text |Cite
|
Sign up to set email alerts
|

Chronically Elevating Circulating Ketones Can Reduce Cardiac Inflammation and Blunt the Development of Heart Failure

Abstract: Background: Previous studies have shown beneficial effects of acute infusion of the primary ketone body, β-hydroxybutyrate, in heart failure (HF). However, whether chronic elevations in circulating ketones are beneficial remains unknown. Methods: To chronically elevate circulating ketones in mice, we deleted the expression of the ketolytic, rate-limiting-enzyme, SCOT (succinyl-CoA:3-ketoacid-CoA transferase 1; encoded by Oxc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(54 citation statements)
references
References 50 publications
3
50
0
1
Order By: Relevance
“…Chronic elevation of circulating ketones by knockout of succinyl-CoA:3-ketoacid-CoA transferase (SCOT)1 in mouse skeletal muscle suppressed pressure overload-induced cardiac inflammation and cardiac dysfunction. Infusion with β-hydroxybutyrate into isolated hearts inhibited NLRP3 inflammasome activation (Byrne et al, 2020b). Inhibiting of sodium-glucose cotransporter (SGLT)2 increased β-hydroxybutyrate and decreased serum insulin in patients with type 2 diabetes compared to sulfonylurea, and inhibited activation of the NLRP3 inflammasome in isolated macrophages (Kim et al, 2020).…”
Section: Preclinical Experiments On Inflammasome Inhibitionmentioning
confidence: 99%
“…Chronic elevation of circulating ketones by knockout of succinyl-CoA:3-ketoacid-CoA transferase (SCOT)1 in mouse skeletal muscle suppressed pressure overload-induced cardiac inflammation and cardiac dysfunction. Infusion with β-hydroxybutyrate into isolated hearts inhibited NLRP3 inflammasome activation (Byrne et al, 2020b). Inhibiting of sodium-glucose cotransporter (SGLT)2 increased β-hydroxybutyrate and decreased serum insulin in patients with type 2 diabetes compared to sulfonylurea, and inhibited activation of the NLRP3 inflammasome in isolated macrophages (Kim et al, 2020).…”
Section: Preclinical Experiments On Inflammasome Inhibitionmentioning
confidence: 99%
“…Another study found that the anti-inflammatory effect of ketogenic diet may be attributed to the β-OHB-mediated inhibition of Nlrp3 inflammasome formation (Youm et al, 2015). Increasing the circulating β-OHB levels by SCOT knockout in skeletal muscle reduced cardiac Nlrp3 inflammasome activation upon heart failure (Byrne et al, 2020). Endoplasmic reticulum (ER) stress can induce Nlrp3 inflammasome.…”
Section: β-Ohb Is An Endogenous Nlrp3 Inflammasome Inhibitormentioning
confidence: 99%
“…Deletion of succinyl-CoA:3-ketoacid-CoA transferase 1 (SCOT) In a mouse model increased circulating ketones and reduced the cardiac inflammasome preventing heart failure caused by increased afterload (30).…”
Section: Discussionmentioning
confidence: 99%